A lithium adsorbent and its preparation method and application

By improving the preparation method of lithium adsorbents, using surfactants and morphological regulators to form a porous structure, the problems of high dissolution and low utilization of lithium adsorbent precursor powder materials in lithium extraction in salt lakes are solved, and adsorption is improved Capacity and efficiency achieve more efficient lithium adsorption performance.

CN118403602BActive Publication Date: 2024-12-27JUNENG YONGTUO (ZHUHAI) TECH DEV CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202410497139.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-24
Publication Date
2024-12-27
Estimated Expiration
2044-04-24

AI Technical Summary

Technical Problem

The precursor of the existing lithium adsorbent is a powder material, which is directly used in salt lakes to extract lithium, and is unable to achieve long-term recycling. The utilization rate of active ingredients after the granulation of organic polymers is low, and the lithium adsorption capacity is Significantly reduced.

Method used

By mixing aluminum salt with lithium salt and adding alkaline solution to stir, surfactant is introduced for surface modification, combining morphological regulators and pore-generating agents, a porous structure is formed, and the granulation process is optimized to improve the active surface area and dispersion of the adsorbent to ensure that lithium ions are effectively embedded in aluminum hydroxide holes.

Benefits of technology

It improves the adsorption capacity and adsorption efficiency of lithium adsorbent, extends the service life, enhances the adsorption performance and dispersion effect of lithium, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004807512460000091
    Figure BDA0004807512460000091
  • Figure BDA0004807512460000092
    Figure BDA0004807512460000092
  • Figure BDA0004807512460000093
    Figure BDA0004807512460000093
Patent Text Reader

Abstract

The invention discloses a lithium adsorbent and a preparation method and application thereof, belonging to the technical field of preparation of new chemical materials. The preparation method comprises the following steps: S1, mixing aluminum salt and lithium salt for reaction, adding alkali solution for stirring and aging to obtain a reaction initial solution; S2, adding a surfactant to the reaction initial solution for stirring and reaction, filtering, and drying the filter residue to obtain a precursor fine powder; S3, adding the precursor fine powder, a binder, a morphology regulator, and a porogen into a solvent for stirring and dissolving to obtain a mixed slurry; S4, extruding the mixed slurry through a noodle machine, baking, and crushing to obtain a finished lithium adsorbent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of preparation of new chemical materials, and in particular to a lithium adsorbent and a preparation method and application thereof. Background Art

[0002] Lithium and its compounds are closely related to people's lives and are used in various industries and fields. They have become important strategic materials for national economy and national defense construction. The proven reserves of lithium resources in China's salt lakes account for as high as 80.54%. The main technologies for extracting lithium from salt lakes include precipitation, ion exchange adsorption, solvent extraction, membrane separation, calcination leaching, solar pond method, and electrochemical method. The adsorption method has certain advantages in lithium extraction efficiency and production cost.

[0003] There are three main types of lithium adsorbents: aluminum-based, manganese-based, and titanium-based. Aluminum-based adsorbent technology is mature and has been used by many well-known companies in large-scale lithium extraction from salt lakes. The current defect of aluminum-based lithium adsorbents is that the precursor is a powder material. If it is directly used for lithium extraction from salt lakes, the dissolution rate is high and it cannot be recycled for a long time. After the precursor powder is granulated with an organic polymer, the problem of high dissolution is solved, but the effective ingredients are wrapped in large quantities, the utilization rate is low, and the lithium adsorption capacity is significantly reduced.

[0004] Therefore, a method for preparing a lithium adsorbent is provided to improve the use efficiency of the precursor after granulation to increase the adsorption capacity after granulation. Summary of the invention

[0005] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention provides a method for preparing a lithium adsorbent, which improves the use efficiency of the precursor after granulation to improve the adsorption capacity and adsorption efficiency after granulation.

[0006] The second aspect of the present invention provides a lithium adsorbent prepared by the above preparation method.

[0007] The third aspect of the present invention provides an application of the lithium adsorbent prepared by the above preparation method.

[0008] According to a first aspect of the present invention, a method for preparing a lithium adsorbent is provided, the method comprising the following steps:

[0009] S1, mixing aluminum salt and lithium salt for reaction, adding alkali solution, stirring and aging to obtain an initial reaction solution;

[0010] S2, adding a surfactant to the initial reaction solution, stirring the reaction, filtering, and drying the filter residue to obtain a precursor fine powder;

[0011] S3, adding the precursor fine powder, binder, morphology control agent, and porogen into a solvent, stirring and dissolving them to obtain a mixed slurry;

[0012] S4, extruding the mixed slurry through a noodle machine, baking, and crushing to obtain a finished lithium adsorbent.

[0013] The method for preparing the lithium adsorbent according to the first embodiment of the present invention has at least the following beneficial effects:

[0014] In the process of preparing the adsorbent precursor, the present invention raises the reaction temperature to above 80° C. to meet the energy requirement of lithium embedding into the holes of aluminum hydroxide, ensuring that all holes of aluminum hydroxide can effectively embed lithium ions to form an effective adsorbent precursor.

[0015] The present invention introduces a surfactant to perform surface modification on the precursor during the preparation of the adsorbent precursor, which is more cost-effective than surface modification of other independent processes and can also improve the affinity of the adsorbent precursor in the organic phase. The surfactant can modify the surface of the inorganic salt to make the inorganic salt more affinity with organic matter, avoid the phenomenon of inorganic salt agglomeration, make it more evenly dispersed in the organic polymer, and improve the dispersibility of the adsorbent in the subsequent granulation step.

[0016] In the present invention, PAN is introduced as a morphology regulator and carbon tetrachloride is introduced as a porogen during the granulation process to form a surface porous structure, effectively increase the active surface area of ​​the adsorbent, and enhance the adsorption performance.

[0017] In the preparation process, the present invention satisfies the activation energy requirement of lithium ion embedding into aluminum hydroxide by precisely controlling the reaction temperature and time, thereby ensuring the high efficiency of the adsorbent. By optimizing the granulation process, it is ensured that the precursor has a better dispersion effect in subsequent applications, thereby increasing the use efficiency of the adsorbent.

[0018] According to some embodiments of the present invention, the aluminum salt is selected from at least one of aluminum trichloride, aluminum chloride, and aluminum sulfate.

[0019] Preferably, the aluminum salt is aluminum trichloride.

[0020] According to some embodiments of the present invention, the lithium salt is selected from at least one of lithium carbonate and lithium chloride.

[0021] Preferably, the lithium salt is selected from lithium carbonate.

[0022] According to some embodiments of the invention, the surfactant is sodium dodecylbenzene sulfonate (SDS).

[0023] The present invention utilizes sodium dodecylbenzene sulfonate (SDS) to modify the surface of the precursor, and achieves a better dispersion effect of the precursor powder during the granulation process by combining it with an organic high molecular polymer, which helps to improve the uniformity of the precursor and the consistency of the particles.

[0024] According to some embodiments of the present invention, the morphology control agent is polyacrylonitrile (PAN) fiber resin.

[0025] The present invention introduces a small amount of polyacrylonitrile (PAN, average molecular weight 50000) fiber resin into the binder as a morphology regulator, which helps to adjust the morphology and structure of the adsorbent, thereby improving the adsorption performance and stability.

[0026] According to some embodiments of the present invention, the binder is chlorinated polyvinyl chloride (CPVC, chlorine content ≥ 65%).

[0027] The present invention uses organic high molecular polymer chlorinated polyvinyl chloride (CPVC) as a binder, which has good chemical stability and mechanical properties, provides a good support structure for the adsorbent, reduces the risk of cracks and breakage of the lithium adsorbent during use, and increases its service life.

[0028] According to some embodiments of the present invention, the porogen is carbon tetrachloride.

[0029] The addition of carbon tetrachloride during the granulation process, which is immiscible with CPVC and miscible with dichloromethane, acts as a porogen, helps to form a porous structure and increase the porosity of the adsorbent.

[0030] According to some embodiments of the invention, the alkali solution comprises at least one of sodium hydroxide, aluminum hydroxide and lithium hydroxide.

[0031] Preferably, the alkali solution is sodium hydroxide.

[0032] According to some embodiments of the invention, the solvent is dichloromethane.

[0033] According to some embodiments of the present invention, in step S1, the pH value is adjusted to 7-8 with alkaline solution.

[0034] According to some embodiments of the present invention, the molar ratio of the aluminum element in the aluminum salt to the lithium element in the lithium salt is 1 to 10:1.

[0035] Preferably, the molar ratio of the aluminum element in the aluminum salt to the lithium element in the lithium salt is 1.8-2.2:1.

[0036] More preferably, the molar ratio of the aluminum element in the aluminum salt to the lithium element in the lithium salt is 2:1.

[0037] According to some embodiments of the present invention, the molar ratio of the surfactant to the lithium salt is 0.5 to 1.5:10.

[0038] Preferably, the molar ratio of the surfactant to the lithium salt is 0.8-1.2:10.

[0039] More preferably, the molar ratio of the surfactant to the lithium salt is 1:10.

[0040] According to some embodiments of the present invention, the mass ratio of the binder to the precursor fine powder is 0.8-1.5:10.

[0041] Preferably, the mass ratio of the binder to the precursor fine powder is 0.9-1.2:10.

[0042] More preferably, the mass ratio of the binder to the precursor fine powder is 1:10.

[0043] According to some embodiments of the present invention, the mass ratio of the morphology control agent to the binder is 0.5-2.0:10.

[0044] Preferably, the mass ratio of the morphology regulating agent to the binder is 1 to 1.5:10.

[0045] More preferably, the mass ratio of the morphology regulating agent to the binder is 1:10.

[0046] According to some embodiments of the present invention, the mass ratio of the porogen to the binder is 4 to 6:10.

[0047] Preferably, the mass ratio of the porogen to the binder is 5:10; it can also be 1:2.

[0048] According to some embodiments of the present invention, the mass ratio of the binder to the solvent is 0.8-1.5:10.

[0049] Preferably, the mass ratio of the binder to the solvent is 1:10.

[0050] Among them, the present invention helps to achieve optimal adsorption performance by limiting and optimizing the material ratio. Compared with the unoptimized ratio, the precise ratio of the present invention helps to improve the structural stability and adsorption performance of the lithium adsorbent, making it more reliable in long-term use.

[0051] According to some embodiments of the present invention, in step S1, the stirring speed is 500-700 r / min.

[0052] Preferably, in step S1, the stirring speed is 600 r / min.

[0053] According to some embodiments of the present invention, in step S1, the aging time is 25 to 35 minutes.

[0054] Preferably, in step S1, the aging time is 30 minutes.

[0055] According to some embodiments of the present invention, in step S1, the reaction temperature is 80-85°C, for example, 80°C, 81°C, 82°C, 83°C, 84°C, or 85°C.

[0056] To meet the activation energy requirement for lithium ion embedding into aluminum hydroxide, which is about 27 kJ.mol -1 , which helps to improve the reaction efficiency and adsorption performance of the adsorbent to lithium. In this temperature range, the reactants are more fully activated to form more active sites, which has a positive effect on improving the final performance of the adsorbent. Compared with lower temperatures, the temperature limit of the present invention significantly improves the reaction conditions, better meets the actual needs in the preparation of lithium adsorbents, and has obvious advantages in improving preparation efficiency and final performance.

[0057] According to some embodiments of the present invention, the particle size D99 of the precursor fine powder obtained in step S2 is less than 160 μm.

[0058] According to some embodiments of the present invention, in step S2, the reaction temperature is 80-85°C, for example, 80°C, 81°C, 82°C, 83°C, 84°C, or 85°C.

[0059] According to some embodiments of the present invention, in step S2, the stirring speed is 500-700 r / min.

[0060] Preferably, in step S2, the stirring speed is 600 r / min.

[0061] According to some embodiments of the present invention, in step S2, the reaction time is 1 to 3 hours.

[0062] Preferably, in step S2, the reaction time is 2 hours.

[0063] According to some embodiments of the present invention, in step S4, the baking temperature is 80-85°C, for example, 80°C, 81°C, 82°C, 83°C, 84°C, or 85°C.

[0064] According to some embodiments of the present invention, in step S4, the baking time is 20 to 30 minutes.

[0065] Preferably, in step S4, the baking time is 20 minutes.

[0066] According to a second aspect of the present invention, a lithium adsorbent obtained by the above-mentioned preparation method is provided, and the particle size of the obtained salt lake brine lithium adsorbent product is 0.8-2.6 mm.

[0067] The lithium adsorbent according to the second aspect of the present invention has at least the following beneficial effects:

[0068] The lithium adsorbent obtained by the present invention is a surface porous material, which helps to improve the porosity of the adsorbent, thereby increasing the adsorption performance of lithium, increasing the active sites, and making the adsorption of lithium more efficient. Compared with traditional adsorbents, this porous structure makes the adsorption rate faster and the adsorption amount larger. By controlling the steps in the preparation method, the particle size range of the obtained lithium adsorbent product is 0.8 to 2.6 mm, which helps to improve the use efficiency of the adsorbent in practical applications.

[0069] According to a third aspect of the present invention, the use of the lithium adsorbent prepared by the above preparation method in recovering lithium from salt lake brine is proposed.

[0070] If there is no special explanation, the actual meaning of “about” in the present invention is that the error is allowed to be within the range of ±2%, for example, about 100 is actually 100±2%×100.

[0071] Other features and advantages of the present invention will be set forth in the description which follows, and in part will be apparent from the description, or may be learned by practice of the present invention. DETAILED DESCRIPTION

[0072] The embodiments of the present invention are described in detail below, and the same or similar reference numerals throughout the embodiments represent the same or similar elements or elements with the same or similar functions. The embodiments described below are exemplary and are only used to explain the present invention, and cannot be understood as limiting the present invention.

[0073] In the description of the present invention, if there is a description of first, second, etc., it is only for the purpose of distinguishing technical features, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features or implicitly indicating the order of the indicated technical features.

[0074] The words "preferably", "more preferably", etc. in the present invention refer to embodiments of the present invention that may provide certain beneficial effects in certain circumstances. However, other embodiments may also be preferred under the same circumstances or other circumstances. In addition, the description of one or more preferred embodiments does not imply that other embodiments are not applicable, nor is it intended to exclude other embodiments from the scope of the present invention.

[0075] When a numerical range is disclosed herein, the above range is considered to be continuous and includes the minimum and maximum values ​​of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be combined. In other words, unless otherwise indicated, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0076] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of the present invention.

[0077] Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0078] Example 1

[0079] This embodiment provides a method for preparing a lithium adsorbent, comprising the following steps:

[0080] 1) 200 g / L aluminum chloride is reacted with 25 g / L lithium carbonate, the atomic ratio of Al:Li is 2:1, and after the reaction is completed, 200 g / L sodium hydroxide is added, the pH value is adjusted to 7-8, the reaction temperature is controlled at 80°C, the stirring speed is 600 r / min, and the aging time is 30 min.

[0081] 2) After the reaction in step 1) is completed, sodium dodecylbenzene sulfonate (SDS) is added, and the molar ratio of the added amount to lithium carbonate is 1:10, the temperature is controlled at 80°C, the stirring speed is 600r / min, the reaction is carried out for 2 hours, and the filter residue is obtained by suction filtration. The filter residue is dried at 80°C and crushed to obtain a fine powder of an adsorbent precursor with a particle size D99 <160μm.

[0082] 3) Granulation: Precursor fine powder, chlorinated polyvinyl chloride (CPVC), and polyacrylonitrile (PAN) are mixed evenly in a ratio of 10:1:0.1, and then carbon tetrachloride and dichloromethane are added and mixed evenly. The mass ratio of carbon tetrachloride to CPVC is 1:2, and the mass ratio of dichloromethane to CPVC is 10:1. The slurry is extruded through a noodle machine and quickly sent into an oven at 80°C for baking for 20 minutes. It is crushed and sieved, and particles with a particle size of 0.8-2.6 mm are taken as the finished lithium adsorbent.

[0083] Example 2

[0084] This embodiment provides a method for preparing a lithium adsorbent, comprising the following steps:

[0085] 1) 200 g / L aluminum chloride is reacted with 25 g / L lithium carbonate, the atomic ratio of Al:Li is 2:1, and after the reaction is completed, 200 g / L sodium hydroxide is added, the pH value is adjusted to 7-8, the reaction temperature is controlled at 80°C, the stirring speed is 600 r / min, and the aging time is 30 min.

[0086] 2) After the reaction in step 1) is completed, sodium dodecylbenzene sulfonate (SDS) is added, and the molar ratio of the added amount to lithium carbonate is 0.5:10, the temperature is controlled at 80°C, the stirring speed is 600r / min, the reaction is carried out for 2 hours, and the filter residue is obtained by suction filtration. The filter residue is dried at 80°C and crushed to obtain a fine powder of an adsorbent precursor with a particle size D99 <160μm.

[0087] 3) Granulation: Precursor fine powder, chlorinated polyvinyl chloride (CPVC), and polyacrylonitrile (PAN) are mixed evenly in a ratio of 10:1:0.1, and then carbon tetrachloride and dichloromethane are added and mixed evenly. The mass ratio of carbon tetrachloride to CPVC is 1:2, and the mass ratio of dichloromethane to CPVC is 10:1. The slurry is extruded through a noodle machine and quickly sent into an oven at 80°C for baking for 20 minutes. It is crushed and sieved, and particles with a particle size of 0.8-2.6 mm are taken as the finished lithium adsorbent.

[0088] Example 3

[0089] This embodiment provides a method for preparing a lithium adsorbent, comprising the following steps:

[0090] 1) 200 g / L aluminum chloride is reacted with 25 g / L lithium carbonate, the atomic ratio of Al:Li is 2:1, and after the reaction is completed, 200 g / L sodium hydroxide is added, the pH value is adjusted to 7-8, the reaction temperature is controlled at 80°C, the stirring speed is 600 r / min, and the aging time is 30 min.

[0091] 2) After the reaction in step 1) is completed, sodium dodecylbenzene sulfonate (SDS) is added, and the molar ratio of the added amount to lithium carbonate is 1.5:10, the temperature is controlled at 80°C, the stirring speed is 600r / min, the reaction is carried out for 2 hours, and the filter residue is obtained by suction filtration. The filter residue is dried at 80°C and crushed to obtain a fine powder of an adsorbent precursor with a particle size D99 <160μm.

[0092] 3) Granulation: Precursor fine powder, chlorinated polyvinyl chloride (CPVC), and polyacrylonitrile (PAN) are mixed evenly in a ratio of 10:1:0.1, and then carbon tetrachloride and dichloromethane are added and mixed evenly. The mass ratio of carbon tetrachloride to CPVC is 1:2, and the mass ratio of dichloromethane to CPVC is 10:1. The slurry is extruded through a noodle machine and quickly sent into an oven at 80°C for baking for 20 minutes. It is crushed and sieved, and particles with a particle size of 0.8-2.6 mm are taken as the finished lithium adsorbent.

[0093] Example 4

[0094] This embodiment provides a method for preparing a lithium adsorbent, comprising the following steps:

[0095] 1) 200 g / L aluminum chloride is reacted with 25 g / L lithium carbonate, the atomic ratio of Al:Li is 2:1, and after the reaction is completed, 200 g / L sodium hydroxide is added, the pH value is adjusted to 7-8, the reaction temperature is controlled at 80°C, the stirring speed is 600 r / min, and the aging time is 30 min.

[0096] 2) After the reaction in step 1) is completed, sodium dodecylbenzene sulfonate (SDS) is added, and the molar ratio of the added amount to lithium carbonate is 1:10, the temperature is controlled at 80°C, the stirring speed is 600r / min, the reaction is carried out for 2 hours, and the filter residue is obtained by suction filtration. The filter residue is dried at 80°C and crushed to obtain a fine powder of an adsorbent precursor with a particle size D99 <160μm.

[0097] 3) Granulation: Precursor fine powder, chlorinated polyvinyl chloride (CPVC), and polyacrylonitrile (PAN) are mixed evenly in a ratio of 10:1:0.05, and then carbon tetrachloride and dichloromethane are added and mixed evenly. The mass ratio of carbon tetrachloride to CPVC is 1:2, and the mass ratio of dichloromethane to CPVC is 10:1. The slurry is extruded through a noodle machine, quickly sent into an oven at 80°C and baked for 20 minutes, crushed and sieved, and particles with a particle size of 0.8-2.6 mm are taken as the finished lithium adsorbent.

[0098] Example 5

[0099] This embodiment provides a method for preparing a lithium adsorbent, comprising the following steps:

[0100] 1) 200 g / L aluminum chloride is reacted with 25 g / L lithium carbonate, the atomic ratio of Al:Li is 2:1, and after the reaction is completed, 200 g / L sodium hydroxide is added, the pH value is adjusted to 7-8, the reaction temperature is controlled at 80°C, the stirring speed is 600 r / min, and the aging time is 30 min.

[0101] 2) After the reaction in step 1) is completed, sodium dodecylbenzene sulfonate (SDS) is added, and the molar ratio of the added amount to lithium carbonate is 0.5:10, the temperature is controlled at 80°C, the stirring speed is 600r / min, the reaction is carried out for 2 hours, and the filter residue is obtained by suction filtration. The filter residue is dried at 80°C and crushed to obtain a fine powder of an adsorbent precursor with a particle size D99 <160μm.

[0102] 3) Granulation: Precursor fine powder, chlorinated polyvinyl chloride (CPVC), and polyacrylonitrile (PAN) are mixed evenly in a ratio of 10:1:0.15, and then carbon tetrachloride and dichloromethane are added and mixed evenly. The mass ratio of carbon tetrachloride to CPVC is 1:2, and the mass ratio of dichloromethane to CPVC is 10:1. The slurry is extruded through a noodle machine and quickly sent into an oven at 80°C for baking for 20 minutes. It is crushed and sieved, and particles with a particle size of 0.8-2.6 mm are taken as the finished lithium adsorbent.

[0103] Example 6

[0104] This embodiment provides a method for preparing a lithium adsorbent, comprising the following steps:

[0105] 1) 200 g / L aluminum chloride is reacted with 25 g / L lithium carbonate, the atomic ratio of Al:Li is 2:1, and after the reaction is completed, 200 g / L sodium hydroxide is added, the pH value is adjusted to 7-8, the reaction temperature is controlled at 80°C, the stirring speed is 600 r / min, and the aging time is 30 min.

[0106] 2) After the reaction in step 1) is completed, sodium dodecylbenzene sulfonate (SDS) is added, and the molar ratio of the added amount to lithium carbonate is 0.5:10, the temperature is controlled at 80°C, the stirring speed is 600r / min, the reaction is carried out for 2 hours, and the filter residue is obtained by suction filtration. The filter residue is dried at 80°C and crushed to obtain a fine powder of an adsorbent precursor with a particle size D99 <160μm.

[0107] 3) Granulation: Precursor fine powder, chlorinated polyvinyl chloride (CPVC), and polyacrylonitrile (PAN) are mixed evenly in a ratio of 10:1:0.1, and then carbon tetrachloride and dichloromethane are added and mixed evenly. The mass ratio of carbon tetrachloride to CPVC is 0.8:2, and the mass ratio of dichloromethane to CPVC is 10:1. The slurry is extruded through a noodle machine, quickly sent into an oven at 80°C and baked for 20 minutes, crushed and sieved, and particles with a particle size of 0.8-2.6 mm are taken as the finished lithium adsorbent.

[0108] Example 7

[0109] This embodiment provides a method for preparing a lithium adsorbent, comprising the following steps:

[0110] 1) 200 g / L aluminum chloride is reacted with 25 g / L lithium carbonate, the atomic ratio of Al:Li is 2:1, and after the reaction is completed, 200 g / L sodium hydroxide is added, the pH value is adjusted to 7-8, the reaction temperature is controlled at 80°C, the stirring speed is 600 r / min, and the aging time is 30 min.

[0111] 2) After the reaction in step 1) is completed, sodium dodecylbenzene sulfonate (SDS) is added, and the molar ratio of the added amount to lithium carbonate is 0.5:10, the temperature is controlled at 80°C, the stirring speed is 600r / min, the reaction is carried out for 2 hours, and the filter residue is obtained by suction filtration. The filter residue is dried at 80°C and crushed to obtain a fine powder of an adsorbent precursor with a particle size D99 <160μm.

[0112] 3) Granulation: Precursor fine powder, chlorinated polyvinyl chloride (CPVC), and polyacrylonitrile (PAN) are mixed evenly in a ratio of 10:1:0.1, and then carbon tetrachloride and dichloromethane are added and mixed evenly. The mass ratio of carbon tetrachloride to CPVC is 1.2:2, and the mass ratio of dichloromethane to CPVC is 10:1. The slurry is extruded through a noodle machine and quickly sent into an oven at 80°C for baking for 20 minutes. It is crushed and sieved, and particles with a particle size of 0.8-2.6 mm are taken as the finished lithium adsorbent.

[0113] Comparative Example 1

[0114] This comparative example provides a method for preparing a lithium adsorbent, which is different from Example 1 in that the reaction temperature in step 1) is 25°C.

[0115] Comparative Example 2

[0116] This comparative example provides a method for preparing a lithium adsorbent, which is different from Example 1 in that the reaction temperature in step 1) is 40°C.

[0117] Comparative Example 3

[0118] This comparative example provides a method for preparing a lithium adsorbent, which is different from Example 1 in that the reaction temperature in step 1) is 60°C.

[0119] Comparative Example 4

[0120] This comparative example provides a method for preparing a lithium adsorbent, which is different from Example 1 in that the reaction temperature in step 1) is 70°C.

[0121] Comparative Example 5

[0122] This comparative example provides a method for preparing a lithium adsorbent, which is different from Example 1 in that the molar ratio of the amount of sodium dodecylbenzene sulfonate added to lithium carbonate in step 2) is adjusted to 0:10.

[0123] Comparative Example 6

[0124] This comparative example provides a method for preparing a lithium adsorbent, which is different from Example 1 in that the mass ratio of PAN to CPVC in step 3) is changed to 0:1.

[0125] Comparative Example 7

[0126] This comparative example provides a method for preparing a lithium adsorbent, which is different from Example 1 in that the mass ratio of carbon tetrachloride to CPVC in step 3) is 0:2.

[0127] Test Case

[0128] The precursors and adsorbents prepared in the above Examples 1 to 7 and Comparative Examples 1 to 7 were used to prepare brine (with a Li content of 600-700 mg / L and a Mg content of 100-120 g / L) for lithium adsorption capacity tests.

[0129] Adsorbent activation: Weigh 10g of sample into a 1L beaker, add deionized water, liquid to solid ratio (W:T) = 100, stir in 55℃ water for more than 3 hours, and take the solution every 1 hour to test the lithium content.

[0130] After activation, the sample was filtered, and the residue was placed in 400 mL of brine (Li content 600-700 mg / L, Mg content 100-120 g / L) and stirred at room temperature (frequency 300 rpm) for 4 hours before filtration. The residue was placed in a 250 mL beaker and deionized water was added. The liquid to solid ratio (W:T) = 10 was stirred in 55 ° C water for 4 hours (frequency 300 rpm), and the diluted solution was tested for Li.

[0131] Li adsorption capacity (mg / g) test: Take 1 mL of the solution before and after adsorption and dilute to 500 mL volumetric flask, i.e. dilute 500 times, and measure the Li content by ICP.

[0132]

[0133] Where: C before adsorption: the concentration of the solution before ICP test adsorption, mg / L; C after adsorption: the concentration of the solution after ICP test adsorption, mg / L;

[0134] Table 1 Lithium adsorption capacity test results of precursor powders prepared at different reaction temperatures

[0135]

[0136] Table 2 Lithium adsorption capacity test results of the finished adsorbents prepared by adding different amounts of SDS in the precursor preparation

[0137]

[0138] Table 3 Test results of lithium adsorption capacity of finished adsorbents prepared by adding different amounts of PAN during granulation

[0139]

[0140] Table 4 Lithium adsorption capacity test results of finished adsorbents prepared by adding different amounts of carbon tetrachloride during granulation

[0141]

[0142] It can be seen that the present invention raises the reaction temperature to above 80°C during the preparation of the adsorbent precursor, meets the energy requirement of lithium embedding into aluminum hydroxide holes, and ensures that all holes in aluminum hydroxide can effectively embed lithium ions to form an effective adsorbent precursor. The present invention introduces a surfactant to modify the surface of the precursor during the preparation of the adsorbent precursor, which is more cost-effective than the surface modification of other independent processes, and can also improve the affinity of the adsorbent precursor in the organic phase. The surfactant can modify the surface of the inorganic salt, so that the inorganic salt can be more affinity with organic matter, avoid the phenomenon of inorganic salt agglomeration, and make it more evenly dispersed in the organic polymer, thereby improving the dispersibility of the adsorbent in the subsequent granulation step. The present invention introduces PAN as a morphology regulator and carbon tetrachloride as a porogen during the granulation process to form a surface porous structure, effectively increase the active surface area of ​​the adsorbent, and enhance the adsorption performance. During the preparation process, the present invention meets the activation energy requirement of lithium ion embedding into aluminum hydroxide by precisely controlling the reaction temperature and time, and ensures the high efficiency of the adsorbent. By optimizing the granulation process, the precursor is ensured to have a better dispersion effect in subsequent applications, which increases the efficiency of the adsorbent.

[0143] The present application achieves a better dispersion effect of the precursor powder during the granulation process by limiting the ratio of the surfactant to the lithium carbonate, thereby improving the uniformity of the precursor and the consistency of the particles; by limiting the ratio of the morphology regulator to the binder, and the ratio of the pore-forming agent to the binder, the utilization efficiency of the precursor after granulation is improved to improve the adsorption capacity and adsorption efficiency after granulation.

[0144] The above is a detailed description of the embodiments of the present invention, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.

Claims

1. A method for preparing a lithium adsorbent, characterized in that: The preparation method comprises the following steps: S1, mixing aluminum salt and lithium salt for reaction, adding alkali solution, stirring and aging to obtain an initial reaction solution; S2, adding a surfactant to the initial reaction solution, stirring, filtering, and drying the filter residue to obtain a precursor fine powder; S3, adding the precursor fine powder, binder, morphology control agent, and porogen into a solvent, stirring and dissolving them to obtain a mixed slurry; S4, extruding the mixed slurry through a noodle machine, baking, and crushing to obtain a finished lithium adsorbent; The molar ratio of the surfactant to the lithium salt is 0.8-1.2:10; the mass ratio of the morphology control agent to the binder is 0.5-2.0:10; the mass ratio of the porogen to the binder is 4-6:10; The surfactant is sodium dodecylbenzene sulfonate; the binder is chlorinated polyvinyl chloride; the morphology regulator is polyacrylonitrile fiber resin; and the porogen is carbon tetrachloride.

2. The preparation method according to claim 1, characterized in that The aluminum salt is selected from at least one of aluminum trichloride, aluminum chloride, and aluminum sulfate.

3. The preparation method according to claim 1, characterized in that The lithium salt is selected from at least one of lithium carbonate and lithium chloride.

4. The preparation method according to claim 1, characterized in that The alkali solution includes at least one of sodium hydroxide, aluminum hydroxide and lithium hydroxide.

5. The preparation method according to claim 1, characterized in that The solvent is dichloromethane.

6. The preparation method according to claim 1, characterized in that The molar ratio of the aluminum element in the aluminum salt to the lithium element in the lithium salt is 1.8 to 2.2:

1.

7. The preparation method according to claim 6, characterized in that The molar ratio of the aluminum element in the aluminum salt to the lithium element in the lithium salt is 2:

1.

8. The preparation method according to claim 1, characterized in that The mass ratio of the binder to the precursor fine powder is 0.8-1.5:

10.

9. The preparation method according to claim 8, characterized in that The mass ratio of the binder to the precursor fine powder is 1:

10.

10. The preparation method according to claim 1, characterized in that The mass ratio of the binder to the solvent is 0.8-1.5:

10.

11. The preparation method according to claim 10, characterized in that The mass ratio of the binder to the solvent is 1:

10.

12. The preparation method according to claim 1, characterized in that The mass ratio of the morphology regulating agent to the binder is 1:

10.

13. The preparation method according to claim 1, characterized in that The mass ratio of the porogen to the binder is 1:

2.

14. The preparation method according to claim 1, characterized in that In step S1, the stirring speed is 500-700 r / min.

15. The preparation method according to claim 1, characterized in that In step S1, the aging time is 25 to 35 minutes.

16. The preparation method according to claim 1, characterized in that In step S1, the reaction temperature is 80-85°C.

17. The preparation method according to claim 1, characterized in that The particle size D99 of the precursor fine powder obtained in step S2 is less than 160 μm.

18. The preparation method according to claim 1, characterized in that In step S2, the reaction temperature is 80-85°C.

19. The preparation method according to claim 1, characterized in that In step S2, the stirring speed is 500-700 r / min.

20. The preparation method according to claim 1, characterized in that In step S2, the reaction time is 1 to 3 hours.

21. The preparation method according to claim 1, characterized in that In step S4, the baking temperature is 80-85°C.

22. The preparation method according to claim 1, characterized in that In step S4, the baking time is 20 to 30 minutes.

23. A lithium adsorbent obtained by the preparation method according to any one of claims 1 to 22, characterized in that: The particle size of the finished product of the salt lake brine lithium extraction adsorbent is 0.8-2.6 mm.

24. Use of the lithium adsorbent obtained by the preparation method according to any one of claims 1 to 22 in recovering lithium from salt lake brine.

Citation Information

Patent Citations

  • Preparation method of granular lithium adsorbent

    CN109225124A

  • Synthesis process of lithium salt adsorbent precursor

    CN114618440A

  • Layered lithium adsorbent powder, preparation method, layered lithium adsorbent particles and application

    CN116966867A

  • Preparation method of lithium ion adsorption material

    CN117563565A

  • Aluminum-series lithium adsorbent, preparation method thereof and application of aluminum-series lithium adsorbent in extraction of lithium from brine

    CN117884104A